Dentinal Changes Caused by in-Office Management of Dentinal Hypersensitivity Using Silver Diamine Fluoride + Potassium Iodide, Laser and Iontophoresis: An Ex-Vivo Study - Nair Nidhi; Jothi Varghese; Vinayak Kamath (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To assess the dentinal tubule sealing ability of silver diamine fluoride solution, laser irradiation, and iontophoresis for the management of dentinal hypersensitivity. Material and Methods: Forty-eight prepared dentin specimens were divided into three groups (n=16): Group A: Laser, Group B: Riva Star and Group C: Iontophoresis. The specimens were treated with the experimental therapeutic modalities and observed under a scanning electron microscope for the estimation of occluded dentinal tubules. Additionally, an energy-dispersive X-ray (EDX) analysis was conducted. The data were statistically evaluated using the Kruskal-Wallis test. Results: The data obtained from SEM analysis showed Group A (Laser) and Group B (Riva Star) had similar efficacy in complete occlusion of the dentinal tubule (p=0.13). However, Group C (Iontophoresis) demonstrated a decreased ability in sealing the dentinal tubules which resulted in statistically significant difference, in comparison to the Laser and Riva Star groups (p=0.002 and p=0.04, respectively). Conclusion: The Laser and Riva Star groups presented superior efficiency in dentinal tubule occlusion ability.